Marketisation of Universities and Legal Education in Poland: The Balance 25 Years After the Transformation - Srokosz, Jacek (University of Wroclaw. Faculty of Law, Administration & Economics, 2016)
This paper is dedicated to the issue of the marketisation of universities and legal education 25 years after the systemic transformation of 1989 where, in public discourse, communist ideology had been replaced by a neo-liberal one. The process of marketisation is perceived as a way to deal with externalities’ where activities in areas traditionally regarded to be of a non-economic nature are being transformed to operate according to market-oriented model (with competitive market, pursuit for profit, economic efficiency, and cost reduction). The mentioned process has encroached into the sphere of higher education where there is observable departure from Humboldt’s model of university and a shift to the Anglo-American model where universities works primarily to prepare graduates to enter the labour market. The case for marketisation and rationalisation of studies is especially palpable in legal education. The article provides an overview of the main crux of the debate between the proponents of the humanist and the practical approaches to legal education in the light of marketisation processes’ in higher education.This paper is dedicated to the issue of the marketisation of universities and legal education 25 years after the systemic transformation of 1989 where, in public discourse, communist ideology had been replaced by a neo-liberal one. The process of marketisation is perceived as a way to deal with externalities’ where activities in areas traditionally regarded to be of a non-economic nature are being transformed to operate according to market-oriented model (with competitive market, pursuit for profit, economic efficiency, and cost reduction). The mentioned process has encroached into the sphere of higher education where there is observable departure from Humboldt’s model of university and a shift to the Anglo-American model where universities works primarily to prepare graduates to enter the labour market. The case for marketisation and rationalisation of studies is especially palpable in legal education. The article provides an overview of the main crux of the debate between the proponents of the humanist and the practical approaches to legal education in the light of marketisation processes’ in higher education.
Keywords: wykształcenie prawnicze; transformacja; Polska po 1989 roku; urynkowienie; uczelnia